2019
DOI: 10.1101/799395
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial suppression and sensitivity for motion in schizophrenia

Abstract: Perceptual spatial suppression is a phenomenon in which the perceived strength of a stimulus in some region of the space is reduced when the stimulus is surrounded by other stimuli. For contrast perception, several studies suggest that spatial suppression is reduced in patients with schizophrenia. For motion perception, only one study has been conducted in a cohort of 16 patients, suggesting that spatial suppression is reduced. It is unknown, however, whether this reduction is related to the lower intelligence… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…This perceptual phenomenon can be explained by an increase of surround inhibition associated with stimulation of the 'far surround' of the neurons' receptive fields [77,78]. Indeed, elderly people [79,80] or individuals with disorders associated with weakened neural inhibition [81][82][83][84] demonstrated decreased spatial suppression.…”
Section: Plos Onementioning
confidence: 99%
“…This perceptual phenomenon can be explained by an increase of surround inhibition associated with stimulation of the 'far surround' of the neurons' receptive fields [77,78]. Indeed, elderly people [79,80] or individuals with disorders associated with weakened neural inhibition [81][82][83][84] demonstrated decreased spatial suppression.…”
Section: Plos Onementioning
confidence: 99%
“…It manifests itself in a longer time needed to discriminate the direction of motion of large high-contrast gratings, compared to small ones. Reduced spatial suppression has been used as a behavioral indication of impaired neural surround inhibition in patients with neuropsychiatric disorders (Foss-Feig et al, 2013; Linares et al, 2020; Serrano-Pedraza et al, 2014; Sysoeva et al, 2017). Surround inhibition, however, is a complex phenomenon that relies on inhibition within primary visual cortex and its top-down regulation by higher-tier cortical areas (Angelucci et al, 2017; Angelucci & Bressloff, 2006; Nurminen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This perceptual phenomenon can be explained by an increase of surround inhibition associated with stimulation of the 'far surround' of the neurons' receptive fields (Angelucci et al, 2017;Nurminen & Angelucci, 2014). Indeed, elderly people (Betts et al, 2005(Betts et al, , 2012 or individuals with disorders associated with weakened neural inhibition (Golomb et al, 2009;Linares et al, 2020;Tadin et al, 2006;Zhuang et al, 2017) demonstrated decreased spatial suppression.…”
Section: Introductionmentioning
confidence: 99%
“…This perceptual suppression corresponds with suppressed neural activity (as measured by fMRI in humans) in early visual areas such as V1 (Chen, 2014; Joo et al, 2012; Nurminen et al, 2009; Pihlaja et al, 2008; Poltoratski et al, 2017; Schallmo et al, 2016; Self et al, 2016; Vanegas et al, 2015; Williams et al, 2003; Zenger-Landolt and Heeger, 2003), consistent with electrophysiological studies in animal models showing suppression of neural responses to stimuli inside the classical receptive field by surrounding stimuli (Angelucci and Bressloff, 2006; Bair et al, 2003; Cavanaugh et al, 2002; Shushruth et al, 2013; Walker et al, 1999; Webb et al, 2005). Studies of surround suppression in people with psychotic disorders have generally shown weaker suppression effects (i.e., reduced illusion strength, or more veridical perception), especially among people with schizophrenia (Barch et al, 2012; Dakin et al, 2005; Schallmo et al, 2015; Serrano-Pedraza et al, 2014; Tadin et al, 2006; Tibber et al, 2013; Yang et al, 2013b; Yoon et al, 2009), and to perhaps a lesser extent among people with bipolar disorder (Schallmo et al, 2015; Yang et al, 2013a); for a meta-analysis, see (Linares et al, 2020). Relatively few studies have examined the physiological basis of reduced surround suppression in psychotic psychopathology; those few have suggested there might be impaired inhibition by GABA (Yoon et al, 2010) and / or reduced neural suppression (Anderson et al, 2017; Seymour et al, 2013) in early visual cortex.…”
Section: Supplemental Informationmentioning
confidence: 99%